Long-term effects of growth hormone replacement therapy in childhood-onset craniopharyngioma: results of the German Craniopharyngioma Registry (HIT-Endo) - Boekhoff, Svenja; Bogusz, Agnieszka; Sterkenburg, Anthe; Eveslage, Maria; Müller, Hermann L. (European journal of endocrinology, 2018)
Objective Quality of survival, prognosis and long-term outcome are often severely impaired in childhood-onset craniopharyngioma (CP) patients. Identification of risk factors for sequelae such as growth hormone (GH) deficiency is important for appropriate treatment and rehabilitation. Design In a cross-sectional study, 79 CP patients recruited in HIT-Endo before 2000 were analyzed according to GH substitution: (a) CP never GH treated (noGH); (b) CP GH treated only during childhood (pedGH); (c) CP under GH, initiated at adulthood (adultGH); (d) CP under GH during childhood and continued during adulthood (contGH). Methods Progression-free (PFS) and overall survival (OS), height, BMI, psychosocial and neuropsychological status (EORTC QLQ-C30, MFI-20). Results OS and PFS rates were similar in all subgroups. ContGH and pedGH CP presented with increases in height (P = 0.002; P = 0.0001) during long-term follow-up when compared with baseline. In all subgroups except for pedGH, increases in BMI were observed when compared with BMI at diagnosis. For emotional functionality and physical fatigue, adultGH CP showed worse (P = 0.037; P = 0.034) response (mean: 61.4%; 12.5%) when compared with pedGH CP (mean: 83.5%; 7.7%). Observed differences were not related to irradiation and hypothalamic involvement. In terms of psychosocial status, no differences were observed between subgroups. Conclusions We conclude that GH substitution was safe with regard to risk of tumor progression/relapse in CP. Growth was improved by GH, whereas the development of obesity was not influenced by GH substitution. However, early initiation of GH substitution after CP diagnosis might have beneficial effects on weight development and neuropsychological outcome.
Gesehen am 02.11.2020